Unsteady Flow of Electrically Conducting Fluid of Second Grade Over A Stretching Sheet Subject to A Transverse Magnetic Field - Ali, Adel (Iraqi Journal of Science, 2024)
In this paper, the series solution for unsteady flow for an incompressible viscous electrically conducting fluid of second grad over a stretching sheet subject to a transverse magnetic field is presented by using homotopy analysis method (HAM). Also we examines the effects of viscoelastic parameter, magnetic parameter and time which they control the equation of motion.